Membangun Niat Pengunjung untuk Berwisata di Gunung Api Purba Ngelanggeran Gunung Kidul - Dhiastama, Rendi Ajib; Udayana, IBN; Lukitaningsih, Ambar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2022)
The research aims to determine the effect of service quality, information quality, system quality and trust on the interest in visiting the Gunung Kidul Purba Volcano tourism object. By knowing the magnitude of the influence of the variables studied, it is hoped that it can provide good recommendations to provide strategies for increasing tourist interest. to visit. The method in this study using the Accidental Sampling method. This research is a quantitative study, the sample in this study is 92 tourists who visit the ancient volcano tourism object. The data collection technique is done by using a questionnaire. The results of this study are that there is a positive and significant effect of service quality on visiting interest, information quality has no significant effect on visiting interest, system quality has a significant effect on visiting interest, trust does not have a significant effect on visiting interest. Simultaneously, service quality, information quality, system quality and trust have a simultaneous effect on visiting interest.